2021
DOI: 10.1111/vru.13018
|View full text |Cite
|
Sign up to set email alerts
|

A simplified CT‐volumetry method for the canine liver

Abstract: Computed tomographic (CT) liver volumetry using the slice addition technique is an accurate, but a time‐consuming method. Commonly used DICOM‐viewing software only allows contouring of one area per image, which can be troublesome in the transverse plane as different lobes are separated. In this prospective, experimental, methods comparison study, we aimed to determine if hepatic contouring using sagittal reformatting and a reduced number of images would yield accurate results. Computed tomographic studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…These findings supported those reported in another study on canine liver CT volumetry, using the same, widely available software. 19 Limitations of the current study include the lack of histopathological confirmation of splenic normalcy and the inability to record splenic weight, due to the retrospective nature of the study and the study population of live patients. Some of these limitations were partially mitigated by performing the pilot studies.…”
Section: Discussionmentioning
confidence: 98%
“…These findings supported those reported in another study on canine liver CT volumetry, using the same, widely available software. 19 Limitations of the current study include the lack of histopathological confirmation of splenic normalcy and the inability to record splenic weight, due to the retrospective nature of the study and the study population of live patients. Some of these limitations were partially mitigated by performing the pilot studies.…”
Section: Discussionmentioning
confidence: 98%
“…In the previous publication evaluating interobserver variability of pulmonary nodule diameter measurement, a CV of 16% was considered a low interobserver variability [ 21 ]. A previous manual CT hepatic volumetry publication used an intraclass correlation coefficient to evaluate interobserver variability, and an intraclass correlation coefficient of 0.957 with 95% confidence interval of 0.908–0.982 was considered excellent [ 22 ]. In the present study, CV of CT hepatic volumetry among three observers was 2.5 (±1.4)%.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a publication on the effect of slice numbers used for CT hepatic volumetry in dogs using sagittal reformatted images [ 22 ]. This study suggested using more than nine slices of sagittal reformatted images to accurately perform CT hepatic volumetry [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations